(NhIMIQ W KRIMINALISTIKE (B:s (NpER(B. (NS WENG(B. /s - (NlEJSTNER(B, (NlASLOs; (NbUJTA[(B, (NpIRO[KAs; (NmI[IN(B, (Ni(B.(Nw(B.s; (NkUZXMIN(B, (Nn(B.(Nm(B.s ((NmOSKWA (B:s (NmIR(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 298s
Keywords: (NsUDEBNO(B-(NHIMI^ESKAQ \KSPERTIZAs